PENGARUH PENERAPAN SUPPLY CHAIN INTEGRATION DI UNIVERSITAS TERHADAP ORGANIZATIONAL PERFORMANCE MELALUI SERVICE QUALITY DAN CUSTOMER SATISFACTION - Dioritto Randy (Business Accounting Review, 2015)
All of enterprises and organizations must pay some attention for its organizational performance. Today some education organization like private universities should also give much regard on various aspect if they want to have better organizational performance. Those aspects are supply chain integration, service quality, and customers’ satisfaction. The goal in this research is to find some relationship between all of those aspects toward organizational performance on private universities in Surabaya. The data analysis used PLS method to 420 respondents from 6 selected private universities in Surabaya.